Complejo de usos mixtos para el desarollo integral (2020)
The M.U.C. (Mixed-Use Complex) for integral development is a project conceived within the urban renewal proposal, Alameda Entre Parques, established by the Alcaldía de Bogotá. The complex houses a cultural and sports center to meet the needs of the self-sufficient community envisioned within the group's intervention. Additionally, it is an urban piece that functions as an extension of the public space in the area, helping achieve a sense of belonging in the inhabitants of the neighborhood.